Prevalence and factors related with the presence of oral manifestations in HIV/AIDS patients who attended health institutions in Cali, Colombia. (Colombia Medica, 2008)
Aim: To determine the prevalence and factors related with the presence of oral manifestations in HIV/AIDS patients who attended health institutions in Cali-Colombia. Materials and methods: A cross-sectional descriptive study was made in 319 patients who attended four health institutions in the city of Cali. The inclusion criteria were: being HIV positive patients, being over 18 years old, attending medical checkups and accepting participation. Pregnant women and inmates were excluded. Results: The general prevalence of oral manifestations was 77.1% (CI 95%: 72.4-81.7). The most frequent oral manifestation was xerostomia with 41.1% (CI 95%: 35.5-46.6), followed by the manifestations from mycotic origin [(35.7% (CI 95% 30.4-41)] bacterial [34.2% (CI 95%: 28.9-39.4)] virals [16.6 (CI 95% 12.5-20.7)], oral ulcers [7.5 (CI 95%: 4.6-10.4)] and neoplastics [3.8 (CI95% 1.6-5.8)]. The population studied did not show non-Hodgkin’s lymphoma. In the multivariate analysis, the presence of oral injuries was associated with time of HIV/AIDS diagnosis during the previous 12 months, detectable viral load, and presence of removable dental prosthesis and self-report of dry mouth. Conclusions: The prevalence of oral manifestations registered in this population is high compared with those reported world-wide. Considering the association found, our results suggest that oral injuries are initial clinic characteristics of the disease and may be useful to predict treatment failure and progression from HIV infection to AIDS.